1996
DOI: 10.1021/ja960001k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropenation and Related Reactions of Ruthenium Vinylidene Complexes

Abstract: Facile deprotonation of a number of cationic ruthenium vinylidene complexes, followed by cyclopropenation, is accomplished in acetone. The deprotonation of [Ru]dCd(Ph)CH 2 R + , ([Ru] ) (η 5 -C 5 H 5 )(PPh 3 ) 2 Ru) by n-Bu 4 -NOH induces a novel cyclization reaction and yields the neutral cyclopropenyl complexes [Ru]-CdC(Ph)CHR (3b, R ) CN; 3c, R ) Ph; 3d, R ) CHdCH 2 ; 3e, R ) CHdCMe 2 ). Complex [Ru]-CdC(C 6 H 9 )CHCN + (3k) is similarly prepared. Protonation of 3b-3e regenerates the corresponding vinyliden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 128 publications
2
44
0
Order By: Relevance
“…As shown in Scheme 2 , the furylruthenium complex 4c was also prepared via deprotonation of the vinylidene complex 2c containing a ethyl acetate at Cγ. Similar reaction has been reported [ 52 ]. Deprotonation reaction of dinuclear vinylideneruthenium complexes containing an ester substituent at Cγ gave the dinuclear bisfuryl complexes [ 49 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As shown in Scheme 2 , the furylruthenium complex 4c was also prepared via deprotonation of the vinylidene complex 2c containing a ethyl acetate at Cγ. Similar reaction has been reported [ 52 ]. Deprotonation reaction of dinuclear vinylideneruthenium complexes containing an ester substituent at Cγ gave the dinuclear bisfuryl complexes [ 49 ].…”
Section: Resultssupporting
confidence: 90%
“…The synthesis of a number of ruthenium cyclopropenyl complexes by deprotonation of readily accessible ruthenium vinylidene complexes containing a CH 2 R group bound to Cβ has been reported [ 49 , 50 , 51 , 52 , 53 ]. A cyclopropenylruthenium complex containing pentamethylcyclopentadiethyl (Cp*) and dppp ligands was synthesized as well [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 By comparison with the extensive photochemical and thermal studies of the 2H-azirine ring system, its behavior toward organometallic reagents has been relatively unexplored. In some earlier work, Alper and Wollowitz 17 demonstrated that group VI metal carbonyls.…”
Section: Methodsmentioning
confidence: 99%
“…Deprotonation of 10 a by nBu 4 NOH inducedt he cyclization reaction to yield the neutralf uryl complex 12 a in 10 min, as shown in Scheme 4. [21] Similarly,d eprotonation of 11 a by nBu 4 NOH yields the NMRobservable neutralf uryl complex 13 a,w hich is unstablea nd readily converts into 14 a quantitativelyt hrough 1,3-benzyl migration. In the 1 HNMR spectrumo f14 a,t he doublet resonance at d = 9.63 ppm is assigned to the aldehyde group, with al ong-range coupling with the pyrrolic hydrogen.…”
Section: Alkylation Versus Nucleophilic Additionmentioning
confidence: 99%